Metabolic Profiling and Gene Expression Analysis Unveil Differences in Flavonoid and Lipid Metabolisms Between ‘Huapi’ Kumquat (Fortunella crassifolia Swingle) and Its Wild Type - Ma, Qiaoli; Hu, Yongwei; Dong, Xinghua; Zhou, Gaofeng; Liu, Xiao; Gu, Qingqing; Wei, Qingjiang (Frontiers in Plant Science, 2021)
To elucidate the mechanism underlying special characteristic differences between a spontaneous seedling mutant ‘Huapi’ kumquat (HP) and its wild type ‘Rongan’ kumquat (RA), the fruit quality, metabolic profiles, and gene expressions of the peel and flesh were comprehensively analyzed. Compared with RA, HP fruit has distinctive phenotypes such as glossy peel, light color, and few amounts of oil glands. Interestingly, HP also accumulated higher flavonoid (approximately 4.1-fold changes) than that of RA. Based on metabolomics analysis, we identified 201 differential compounds including 65 flavonoids and 37 lipids. Most of the differential flavonoids were glycosylated by hexoside and accumulated higher contents in the peel but lower in the flesh of HP than those of RA fruit. For differential lipids, most of them belonged to LysoPCs and LysoPEs, and exhibited low abundance in both peel and flesh of HP fruit. In addition, structural genes associated with the flavonoid and lipid pathways were differentially regulated between the two kumquat varieties. Gene expression analysis also revealed the significant roles of UDP-glycosyltransferase (UGT) and phospholipase genes in flavonoid and glycerophospholipid metabolisms, respectively. These findings provide valuable information for interpreting the mutation mechanism of HP kumquat.